Analysis of the Effect of the Number of Entities, Gross Contribution, and Investment Yield on the Density of Indonesian Communities in Using Sharia Insurance - Ayu Lestari; Fauzi Arif Lubis; Atika (Dinasti Publisher, 2024)
This study aims to examine the relationship between the number of entities, Gross Contributions, and Investment Yield on the density of people using Islamic insurance. The type of research used by researchers is quantitative using secondary data derived from the Non-Bank Financial Industry (IKNB) which consists of 12 samples in 2021-2023. The data collection technique used in this case is indirect observation such as literature studies through books, journals and relevant studies on the research. In the research test used, namely multiple linear regression analysis. Based on the partial effect, that this study shows a significant negative relationship between the Number of Entities on Sharia Insurance Density in Indonesia, it is obtained that the significance value is 0.000 <0.05 with a variable coefficient of -4.610. Where T count is -4.3821 with T table which is 2.201. Based on the partial effect, that this study shows a significant positive relationship between gross contributions to Islamic Insurance Density in Indonesia, it is obtained that the significance value is 0.000 <0.05 with a variable coefficient of 6.064. Where T count is 5.2907 with T table of 2.201. Based on the partial effect, that this study shows there is no relationship between investment yield (investment return) on Sharia Insurance Density in Indonesia, obtained a significance value of 0.990> 0.05 with a variable coefficient of -1.837. Where T count 0.000 with T table is 2.201. Based on the simultaneous influence, the statistical results explain that simultaneously there is a positive and significant effect of the variable Number of Entities, Gross Contributions, and Investment Yield on the Density of Islamic Insurance in Indonesia, significantly amounting to 0.000 <0.05.